EFFECT OF WORKLOAD AND WORK-FAMILY CONFLICT ON EMPLOYEE PERFORMANCE - Dharmawan, Donny; Balla Wahyu Budiarto; Syamsul Hadi; Joko Rianto; Bella Suci Novitri (Bajang Institute, 2024)
The aim of this research is to analyze effect of workload and work-family conflict on employee performance. The type of research used in this research is quantitative research. Population in this study were employees of PT Prudential Life Assurance. Sampling technique in this research used a saturated sampling technique. So the research sample in this study was 100. The data analysis method to answer the hypothesis uses multiple linear regression. The research results show that workload has a negative and insignificant effect on employee performance. Work-family conflict has a negative and significant effect on employee performance.